Acute high-risk pulmonary embolism requiring thrombolytic therapy in a COVID-19 pneumonia patient despite intermediate dosing deep vein thromboprophylaxis (2020)
Cytokine storm induced by the coronavirus 19 (COVID-19) profoundly activates the coagulation cascade causing venous thromboembolism (VTE). Initial studies from Wuhan, China showed increased incidence of VTE in patients with no standard deep vein thrombosis (DVT) prophylaxis in COVID-19 pneumonia patients. Few have argued for high intensity or intermediate DVT prophylaxis in COVID-19 patients with the incidence of VTE ranging from 16-27% despite standard DVT prophylaxis. However, no guideline recommendations presently exist to prescribe augmented DVT prophylaxis in these patients due to lack of evidence although the risk of VTE was clearly demonstrated. While there are ongoing trials to demonstrate the efficacy of intermediate dosing against standard DVT prophylaxis in the prevention of VTE, we present a 36-year-old male admitted with COVID-19 pneumonia who developed acute high-risk pulmonary embolism (PE) requiring emergent thrombolytic therapy despite intermediate dosing DVT prophylaxis.